Stabilizing Interface pH by N‐Modified Graphdiyne for Dendrite‐Free and High‐Rate Aqueous Zn‐Ion Batteries. Issue 6 (20th December 2021) - Yang, Qi; Li, Liang; Hussain, Tanveer; Wang, Donghong; Hui, Lan; Guo, Ying; Liang, Guojin; Li, Xinliang; Chen, Ze; Huang, Zhaodong; Li, Yongjun; Xue, Yurui; et al.
Abstract: Zn dendrite issue was intensively studied via tuning zinc ion flux. pH change seriously influences dendrite formation, while its importance has not been revealed. Here, we construct a N‐modification graphdiyne interface (NGI) to stabilize pH by mediating hydrated zinc ion desolvation. Operando pH detection reveals pH stabilization by NGI. This works with pores in NGI to achieve dendrite‐free Zn deposition and an increased symmetric cell lifespan by 116 times. Experimental and theoretical results owe pH stabilization to desolvation with a reduced activation energy achieved by electron transfer from solvation sheath to N atom. The efficient desolvation ensures that electron directly transfers from substrate to Zn 2+ (rather than the coordinated H2 O), avoiding O−H bond splitting. Hence, Zn‐V6 O13 battery achieves a long lifespan at 20.65 mA cm −2 and 1.07 mAh cm −2 . This work reveals the significance of interface pH and provides a new approach to address Zn dendrite issue. Abstract : Interface pH change seriously influences dendrite formation, while its importance has not been revealed. We constructed a N‐modification graphdiyne interface to stabilize pH by accelerating hydrated zinc ions desolvation, enabling the direct electron transfer from anode to Zn 2+ (rather than the coordinated H2 O). Operando pH detection reveals the pH stabilization. Zn‐V6 O13 battery works well at 20.65 mA cm −2 and 1.07 mAh cm −2 . This work highlights interface pH and provides a new approach to address Zn dendrite issue.